Holocene Crab Consumption at Watinglo, Papua New Guinea - Hendri Asyhari Fajrian Kaharudin (Badan Riset dan Inovasi Nasional, 2023)
Malacostraca are commonly found in coastal archaeological sites in the Indo-Pacific; both swimming and terrestrial crabs. This archaeological evidence as well as ethnographic studies indicate that they formed an important component of the human diet in the past as they still do in many regions today. However, they often go unidentified and largely unanalysed in archaeological research due to the highly fragmentary state of the remains and the associated difficulties posed for identification and quantification. Here we discuss these issues and provide an example of crab remains recovered from a coastal archaeological site in Papua New Guinea, Watinglo shelter, with an occupation record spanning from the Terminal Pleistocene to historic times. We also briefly compare these finding to crab remains from archaeological sites of similar antiquity in Indonesia and the Philippines.